Modeling population harvesting of rodents for the control of hantavirus infection - F.M.Yusof,; A.I.B. Md. Ismail,; N.H.M. Ali, (Universiti Kebangsaan Malaysia, 2010)
Hantaviruses are infectious agents that can cause diseases resulting in deaths in humans and are hosted by rodents without affecting the hosts themselves. A simple mathematical model describing the spread of the Hantavirus infection in rodents has been proposed and developed by Abramson and Kenkre where the model takes into account the temporal and spatial characteristics of this infection. In this paper, we extended this model to include the process of harvesting and study the impact of different harvesting strategies in the spread of the Hantavirus infection in rodents. Several numerical simulations were carried out and the results are discussed.